Los conectores pragmáticos en el habla culta costarricense - Solano Rojas, Yamilet (Universidad de Costa Rica, 2015)
Expressions such as bueno, idiay, verdad, digamos.fijáte, etc., which reccurvery frequendy in spokenCosta Rican Spanish, traditionalIy have been stigrnatized as pet words without much meaning orfunction. On the basis of data from recorded interviews, cooversations and lectures, the author of theartic1e posits that they are pragmatic connectors with important phatic and discourse organizingfunctions which make them necessary and even obligatory in spontaneous speech. This explains whyalI speakers, inc1uding those aware of the fact that they are coosidered "errors", keep using them.